Bemisia tabaci in Iraq: Population structure, endosymbiont diversity and putative species. (23rd February 2020) - Kareem, Ali A.; Logan, Samuel A.; Port, Gordon; Wolff, Kirsten
Abstract: Whiteflies (Hemiptera: Aleyrodidae) are major pests of many crops worldwide. Bemisia tabaci is a cryptic species complex composed of more than 39 putative species. Understanding which putative species of B. tabaci are predominant in an area is vital for effective pest management since they may vary considerably with respect to insecticide resistance, host plant range and virus transmission. Here, for the first time, the genetic diversity, the symbiont diversity and population structure of B. tabaci in Iraq were studied. Fourteen populations were analysed using mitochondrial cytochrome C oxidase subunit 1 (mtCO1) sequencing and microsatellite genotyping. Symbiotic bacteria were identified using 16S rRNA and 23S rRNA sequencing. MtCO1 sequencing detected two putative species of B. tabaci . The predominant putative species in Iraq was Middle East‐Asia Minor (MEAM) 1 subcladeB2. In addition, one individual was MEAM1‐subcladeB. The second putative species was a single individual of MEAM2. The microsatellite data indicated low genetic diversity, with no biologically informative clustering. All MEAM1 individuals harboured one primary symbiont, Portiera aleyrodidarum, and most (96%) have two secondary symbionts: Hamiltonella sp. and Rickettsia sp. This study has identified the genetic diversity and population structure of B. tabaci in Iraq. Further investigation is needed to update the pest status of B. tabaci in this region. The current data, combined with investigations into the capacity of the various putative species to transmit plant viruses, especially tomato yellow leaf curl virus, will aid pest management and horticultural production.